Proteolytic activity of three probiotic strains in semi-hard cheese as single and mixed cultures: Lactobacillus acidophilus, Lactobacillus paracasei and Bifidobacterium lactis - Bergamini, Carina Viviana (2009)
The influence of three probiotic strains (Lactobacillus acidophilus, Lactobacillus paracasei and Bifidobacterium lactis) in semi-hard cheese proteolysis patterns was assessed. Probiotics were inoculated both as single cultures and as a three-strains mix, and added to milk by two different techniques: after a pre-incubation step or directly to vat. B. lactis did not show any effect on proteolysis of cheeses, while L. paracasei showed a little impact at the end of the ripening. On the contrary, L. acidophilus significantly influenced secondary proteolysis from the beginning of ripening, causing an increase in the levels of small nitrogen-containing compounds and free amino acids and changes in the peptide profiles. Lactobacillus acidophilus effect on peptidolysis was more noticeable when it was added to cheese-milk after pre-incubation in an enriched milk-fat substrate. Similar results obtained with the three-strain mixed culture suggest that L. acidophilus played a major role in secondary proteolysis of probiotic cheeses in this trial.